2021
DOI: 10.1177/0002764221989772
|View full text |Cite
|
Sign up to set email alerts
|

This Account Doesn’t Exist: Tweet Decay and the Politics of Deletion in the Brexit Debate

Abstract: Literature on influence operations has identified metrics that are indicative of social media manipulation, but few studies have explored the lifecycle of low-quality information. We contribute to this literature by reconstructing nearly 3 million messages posted by 1 million users in the last days of the Brexit referendum campaign. While previous studies have found that on average only 4% of tweets disappear, we found that 33% of the tweets leading up to the referendum vote are no longer available. Only about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…About 3.5% of the tracked scholarly tweets became unavailable at some point in a period of 56 days. This is a small percentage, but it may be a nontrivial amount when working with older and larger sets of tweets, or tweets related to controversial topics or accounts whose deletion or suspension 8 would lead to a cascade of related Twitter data becoming unavailable (Bastos, 2021; Fang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…About 3.5% of the tracked scholarly tweets became unavailable at some point in a period of 56 days. This is a small percentage, but it may be a nontrivial amount when working with older and larger sets of tweets, or tweets related to controversial topics or accounts whose deletion or suspension 8 would lead to a cascade of related Twitter data becoming unavailable (Bastos, 2021; Fang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, Zubiaga (2018) rechecked the completeness of 30 Twitter datasets associated with different real‐world events posted between 2012 and 2016, finding that, on the whole, 18.6% of the tweets were unavailable during the data rechecking. Bastos (2021) reported that 33% of the nearly 3 million tweets about the Brexit referendum posted in 2016 were no longer available 3 years after the vote. In addition, by rechecking the 42.5 million scholarly tweets recorded by http://altmetric.com until October 2017, Fang et al (2020) found that 13% of the tweets had become unavailable by September 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Six of these 10 most shared links were unavailable at the time of the analysis. Given the opaqueness and the politics of deletion implemented by these platforms, relying on social media data as a record for public deliberations can indeed be difficult (Bastos, 2021). Notwithstanding, not all types of problematic content are removed by the platforms and not only fake content and disinformation are deleted.…”
Section: The Dynamics Of Hyperlinking In the Anti-soros Campaignsmentioning
confidence: 99%
“…Perhaps more worryingly, there are more messages associated with the Leave campaign that disappeared than the entire universe of tweets affiliated with the Remain campaign (Bastos, 2021c). In fact, the list of hashtags tweeted over one thousand times with a deletion rate of 40% or higher is largely restricted to Leave terms: voteleave , votein , leaveeu , ivoted , voteout , beleave , cameron , inorout , ukip and eng .…”
Section: We Cannot Know What We Do Not Knowmentioning
confidence: 99%
“…Lastly, even if the rapid turnover and short shelf life of social media content constitute an expected affordance of social media communication, it is hardly a desirable design of political communication and deliberation across social platforms that may be further subjected to Editorial artificial manipulation and false amplification. In other words, while the short shelf life of social media posts may be a reasonable expectation, as is the expectation that one should have control over its own personal data (Ausloos, 2012), this poses considerable challenges for deliberation and informed public debate around matters where the issue being deliberated on is constantly disappearing from public scrutiny (Bastos, 2021c).…”
Section: Editorialmentioning
confidence: 99%